cAMP Catalyzing Phosphodiesterases Control Cholinergic Muscular Activity But Their Inhibition Does Not Enhance 5-HT4 Receptor-Mediated Facilitation of Cholinergic Contractions in the Murine Gastrointestinal Tract - Pauwelyn, Vicky; Lefebvre, Romain A. (Frontiers in Pharmacology, 2018)
Background: As the signal transduction of 5-HT4 receptors on cholinergic neurons innervating smooth muscle is controlled by phosphodiesterase (PDE) 4 in porcine stomach and colon and human large intestine, the in vivo gastroprokinetic effects of a 5-HT4 receptor agonist might be enhanced by combination with a selective PDE4 inhibitor. The presence of 5-HT4 receptors on cholinergic neurons towards murine gastrointestinal circular muscle was recently shown. If the control of this receptor pathway by PDE4 is also present in mice, this might be a good model for in vivo testing of the combination therapy. Therefore this study investigates the role of cAMP catalyzing PDEs in smooth muscle cell activity and in the intraneuronal signal transduction of the 5-HT4 receptors in the gastrointestinal tract of C57Bl/6J mice. Methods: In circular smooth muscle strips from murine fundus, jejunum and colon, submaximal cholinergic contractions were induced by either electrical field stimulation (EFS) or by carbachol (muscarinic receptor agonist). The influence of the PDE inhibitors IBMX (non-selective), vinpocetine (PDE1), EHNA (PDE2), cilostamide (PDE3) and rolipram (PDE4) was tested on these contractions and on the facilitating effect of a submaximal concentration of prucalopride (5-HT4 receptor agonist) on EFS-induced contractions. Results: In the 3 gastrointestinal regions, IBMX and cilostamide concentration-dependently decreased carbachol- as well as EFS-induced contractions. Some inhibitory effect was also observed with rolipram. In the fundus a non-significant trend for an enhancement of the facilitating effect of prucalopride on EFS-induced contractions was observed with IBMX, but none of the selective PDE inhibitors enhanced the facilitating effect of prucalopride in fundus, jejunum or colon. Conclusions: In analogy with the porcine gastrointestinal tract, in murine fundus, jejunum and colon circular smooth muscle PDE3 is the main regulator of the cAMP turnover, with some contribution of PDE4. In contrast to the porcine gastrointestinal tract, the in vitro facilitation of electrically induced cholinergic contractions by 5-HT4 receptor stimulation could not be enhanced by specific PDE inhibition. The C57Bl/6J murine model is thus not suitable for in vivo testing of a 5-HT4 receptor agonist combined with a selective PDE4 inhibitor.